Linkages Between Value Based Performance Measurements and Risk Return Trade Off: Theory and Evidence - Celik, Saban (2011)
In this study we attempt to investigate the linkages between value-based performance measurements and risk-return trade off in a way to explain cross sectional asset returns. On the side of value based performance measurements, three groups of variables are used as a sorting factor: traditional measures which consist of accounting based and market based; recently popularized measures such as Economic Value Added and Market Value Added and theoretically sound measures such as foreign investor allocation and firm systematic risk indicators. The goals of the study are (i) to show how value based measurements techniques relate to risk return trade off and (ii) how these measures affect the cross sectional asset returns in manufacturing industry. Empirical results indicate that foreign investor allocation as a sorting factor produces much more meaningful risk return positive linear relation for cross sectional asset returns than traditional and recently popularized measures